Characterisation of putative retrotrapezoid nucleus (RTN) chemoreceptor neurons in the adult human brainstem - Yazhou Liu; Rita Machaalani; Irit Markus; Claire E. Shepherd; Natasha N. Kumar (Brain Structure and Function, 2025)
The retrotrapezoid nucleus (RTN) of rodents is located ventral to the facial motor nucleus (7N) and consists of acid-sensitive neurons that activate breathing and mediate the central component of the ventilatory response to hypercapnia. In rodents, RTN neurons can be histologically identified by the presence of paired-like homeobox 2B positive nuclei (Phox2b +) and the absence of cytoplasmic choline acetyltransferase (ChAT-) and tyrosine hydroxylase (TH-). Up to 50% of rodent RTN neurons synthesise galanin, and 88% express pituitary adenylate cyclase activating polypeptide (PACAP). The human RTN (hRTN) has not been mapped to date. This study aimed to map the location and cytoarchitecture of the adult hRTN and compare the findings to the homologies of rodents, macaques and human infants. Formalin-fixed, paraffin-embedded tissue blocks from two adult cases, spanning the medulla-pons, were serially sectioned (10 µm thick) and every four in thirty sections was assayed for immunohistochemistry for ChAT, or double-labelled Phox2b/TH, Phox2b/galanin and Phox2b/PACAP, followed by analysis using QuPath software. hRTN neurons, identified as Phox2b + /TH-/ChAT-, were located ventral to 7N and lateral to the superior olive, overlapped with the C1 or A5 catecholaminergic population and extended rostrocaudally from Obex + 13 to + 17 mm. In the parafacial area, 90% of Phox2b immunoreactive (-ir) neurons are hRTN neurons, totaling around 5000 bilaterally, and were surrounded by numerous TH-ir fibers. Galanin- and PACAP-ir was identified in 43% and 39% of Phox2b-ir parafacial neurons, respectively. This is the first study to characterise and quantitatively map the adult human RTN using a series of neurochemical markers.

Astrocyte-derived lactate/NADH alters methamphetamine-induced memory consolidation and retrieval by regulating neuronal synaptic plasticity in the dorsal hippocampus - Xu Tan; Xiaoyu Liu; E Liu; Min Liu; Shouhong Mu; Zhaofang Hang; Weikai Han; Tingting Wang; Yang Zhang; Jing Zhang; Qingwei Yue; Jinhao Sun (Brain Structure and Function, 2022)

Characterization of electrocorticogram high-gamma signal in response to varying upper extremity movement velocity - Po T. Wang; Colin M. McCrimmon; Christine E. King; Susan J. Shaw; David E. Millett; Hui Gong; Luis A. Chui; Charles Y. Liu; Zoran Nenadic; An H. Do (Brain Structure and Function, 2017)